191k views
22 votes
What is the value of the expression when a = -2, b = 3, and c = -6?
ab + 2c
-bc

User Stiver
by
5.9k points

1 Answer

14 votes

Answer:

0

Explanation:

Start by substituting in the values given

ab + 2c - bc

(-2)(3) + 2(-6) - (3)(-6) start by multiplying from left to right

-6 + 2(-6) - (3)(-6)

-6 + -12 - (3)(-6)

-6 + -12 - -18 when you minus a negative it is like adding a positive so turn the two minus symbols into a plus sign. only di this. step if you learned it yet.

-18 + 18 = 0

User Pcent
by
5.6k points